2010
DOI: 10.1186/1471-2164-11-598
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide survey and analysis of microsatellites in nematodes, with a focus on the plant-parasitic species Meloidogyne incognita

Abstract: BackgroundMicrosatellites are the most popular source of molecular markers for studying population genetic variation in eukaryotes. However, few data are currently available about their genomic distribution and abundance across the phylum Nematoda. The recent completion of the genomes of several nematode species, including Meloidogyne incognita, a major agricultural pest worldwide, now opens the way for a comparative survey and analysis of microsatellites in these organisms.ResultsUsing MsatFinder, the total n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 47 publications
7
30
0
1
Order By: Relevance
“…Some studies also revealed that trinucleotide repeats were predominant in most insect genomes (Castagnone-Sereno et al, 2010;Wang et al, 2008). However, tetranucleotides in contrast to dinucleotides, appeared significantly overrepresented in G. gallus, M. gallopavo, G. Fortis, and C. livia.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Some studies also revealed that trinucleotide repeats were predominant in most insect genomes (Castagnone-Sereno et al, 2010;Wang et al, 2008). However, tetranucleotides in contrast to dinucleotides, appeared significantly overrepresented in G. gallus, M. gallopavo, G. Fortis, and C. livia.…”
Section: Discussionmentioning
confidence: 93%
“…Such a propensity may be to suppress the other categories of SSRs, thus reducing the incidence of frameshift mutations in coding regions caused by nontriplet repeats (Metzgar et al, 2000;Labbe et al, 2011). What's more, microsatellites which are located in coding regions may affect evolution of protein structure and function in this species (Castagnone-Sereno et al, 2010). Our study of SSRs in G. gallus and five other bird species genomes is a significant step towards a better understanding of the nature of these important sequences.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Microsatellites markers are widely used to infer information about dispersal, relatedness, effective population size, parentage, etc. [7], but until recently their development was complex, time-consuming and expensive [8]. Here, we aimed to develop microsatellite markers for S. obvelata to allow insights into the population biology of this important parasite.…”
Section: Introductionmentioning
confidence: 99%